Особенности размножения антилопы канны (Taurotragus oryx Pall.) в условиях полувольного разведения в Аскании-Нова - Стекленев, Е.П. (Вестник зоологии, 1969)
The period of sex activity in Taurotragus eryx Pall, under conditions of «Aska-niya-Nova» zoological gardens coincides with spring-summer season of the year. The greatest number of females comes in heat in May — July. Estrus cycles in females reached puberty proceed in all seasons of the year, though in autumn and winter these cycles are not accompanied by sex reflexes. Spermatogenesis in males also takes place the whole year round with some tendency to decreasing generative processes at the end of summer and in autumn. The duration of a sex cycle in Taurotragus oryx Pall, females is equal Jo 22.16±0.04 days (with variations from 22 to 23 days); the duration of estrus is 1.5— 2 days and that of heat — three—five hours. The puberty in most of females comes after they are two years old, though the cases, when females come in heat being 15—16 months old, are not seldom. The puberty of males comes, approximately at the same age. The individuals of both sexes reach the physiological maturity being three years old.